Coupling first-order phase transitions to curvature-squared inflation - Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 1992)
A new way to couple first-order phase transitions to inflation is proposed. The mechanism, dubbed getaway inflation, bypasses the problem of the "graceful exit" by letting the inflationary phase of the background have a classical end. At the same time, a stage of bubble production via semiclassical tunneling occurs, allowing speculations on the role of bubbles on the early structure formation. A realization of the proposed process is found in a nonminimally coupled higher-order gravity theory which by itself deserves further investigation.
Gesehen am 22.11.2017